Exploring TESOL teacher educators as learners and reflective scholars: A shared narrative inquiry. Issue 4 (7th December 2019) - Peercy, Megan Madigan; Sharkey, Judy; Baecher, Laura; Motha, Suhanthie; Varghese, Manka
Abstract : Recent scholarship examining how teachers and teacher educators learn to teach has advocated for a more critically oriented and better developed pedagogy of teacher education, in which teacher educator as practitioner is both in evidence and examined. Yet we currently know little about teacher educators as learners and reflective scholars open to examining their practice and research, and such inquiry is particularly limited within the scholarship in English language teacher education. This article brings together the narratives of the five co‐authors, all TESOL teacher educators based in U.S. universities who examine questions about the intersections of their identities and pedagogies. They do so as a first step toward addressing the gap in the literature regarding the self‐reflexivity of teacher educators. Identifying themes related to the intertwining of their social and professional identities and their pedagogies, their perceived legitimacy as teacher educators, and the impact of multiple contexts on their identities and pedagogies, the five co‐authors consider how they are both domesticating and domesticated by teacher education (Morgan, 2016) and argue that when teacher educators engage in shared and transparent exploration of their identities and pedagogies they are better able to identify their pedagogical blind spots and opportunities to agentively leverage their identities to challenge dominant discourses.